2017
DOI: 10.1007/978-1-4939-6993-7_4
|View full text |Cite
|
Sign up to set email alerts
|

Compartment-Specific Poly-ADP-Ribose Formation as a Biosensor for Subcellular NAD Pools

Abstract: Nicotinamide adenine dinucleotide (NAD) is vital to many cellular processes and is distributed between distinct subcellular pools in the compartmentalized eukaryotic cell. The detection and relative quantification of these individual pools is difficult because of the methods usually applied, which require cell disruption and fractionation.Here, we describe an immunochemical method to visualize and relatively quantify subcellular NAD pools, which relies on the NAD-consuming activity of poly-ADP-ribose polymeras… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 11 publications
0
12
0
Order By: Relevance
“…Several approaches have been developed to try to quantify NAD + availability in different subcellular compartments. Compartment-targeted expression of the catalytic domain of ADP-ribosyltransferase diphtheria toxin-like 1 (ARTD1, formerly called PARP1) has been used as a molecular detector of NAD + because formation of poly-ADP-ribose, which can be detected by immunofluorescence, functions as a proxy for NAD + availability [11,12]. In addition, NAD + metabolite tracing methods have been developed that quantify NAD + and NADH levels, and define how their ratios in different subcellular compartments under several stress conditions change [11,13,14,15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several approaches have been developed to try to quantify NAD + availability in different subcellular compartments. Compartment-targeted expression of the catalytic domain of ADP-ribosyltransferase diphtheria toxin-like 1 (ARTD1, formerly called PARP1) has been used as a molecular detector of NAD + because formation of poly-ADP-ribose, which can be detected by immunofluorescence, functions as a proxy for NAD + availability [11,12]. In addition, NAD + metabolite tracing methods have been developed that quantify NAD + and NADH levels, and define how their ratios in different subcellular compartments under several stress conditions change [11,13,14,15].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, NAD + metabolite tracing methods have been developed that quantify NAD + and NADH levels, and define how their ratios in different subcellular compartments under several stress conditions change [11,13,14,15]. Free NAD + has been measured in almost all organelles, including the mitochondria, peroxisomes, the endoplasmic reticulum (ER), and the Golgi complex [11,12,13]. These measurements have revealed that steady state NAD + concentrations, as well as changes in NAD + concentrations in response to different stimuli, vary considerably between different subcellular compartments.…”
Section: Introductionmentioning
confidence: 99%
“…Several approaches have been attempted to visualize subcellular distribution of NAD + pools. For example, targeted expression of PARP-1 can be used as a molecular NAD + detector since the presence of NAD + can be visualized by the formation of immunodetectable poly-ADP-ribose (Dölle, Niere, Lohndal, & Ziegler, 2010;VanLinden, Niere, Nikiforov, Ziegler, & Dölle, 2017). Moreover, several genetically encoded NAD + biosensors have been developed, which contain a bipartite NAD + -binding domain derived from bacterial NAD + -dependent DNA ligase fused to a circularly permuted Venus fluorescent protein (cpVenus) (Cambronne et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…These NAD + biosensors can be expressed either in nucleus or in cytoplasm and exhibit reduction in their fluorescent signals upon binding to NAD + . With these powerful molecular tools, NAD + has been detected in the nucleus and almost all cytoplasmic organelles, including mitochondria, peroxisomes, endoplasmic reticulum (ER), and Golgi complex (Cambronne et al, 2016;Dölle et al, 2010;VanLinden et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Besides the nucleus, cytosol and mitochondria, NAD + has also been detected in other subcellular compartments including the peroxisomes and the endoplasmic reticulum (ER) 52,53 .…”
Section: Introductionmentioning
confidence: 99%